THE EFFECT OF CAPITAL STRUCTURE, NET PROFIT MARGIN, TAX PLANNING, AND COMPANY SIZE ON THE VALUE OF BUMN COMPANIES - Adam Afiezan; Beatrice Beatrice; Angelica Angelica; Patricia Fancella (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
Background : Find the components that most influence the self-esteem of public state-owned companies. The research method uses quantitative descriptive while the data collection technique is from secondary data, namely financial reports which are downloaded from the IDX website. The population of public BUMN is 20 companies, with a sample that meets the criteria there are 17 companies. Data processing uses multiple linear regression techniques that must meet a good classical assumption. Method : This study uses a deductive approach, which is a form of scientific presentation from the general to the specific form. Meanwhile, according to its type, this research is a quantitative research because it uses measurable information that is obtained from the financial reports of BUMN companies.. Result : The results of data processing produce factors that positively affect firm value, namely net profit margins and tax planning, firm size negatively affects firm value, while capital structure does not affect firm value.. Conclusions : Simultaneously, the variables will have a significant influence on the company's value with the magnitude of this influence of 37.2%..